Osteoimmunomodulation role of exosomes derived from immune cells on osseointegration - Xiao, Yunchao; Ding, Yanshu; Zhuang, Jingwen; Sun, Ruoyue; Sun, Hui; Bai, Long (Frontiers in Bioengineering and Biotechnology, 2022)
Despite the high success rate of biomedical implants adopted clinically, implant failures caused by aseptic loosening still raise the risk of secondary surgery and a substantial economic burden to patients. Improving the stable combination between the implant and the host bone tissue, achieving fast and high-quality osseointegration can effectively reduce the probability of aseptic loosening. Accumulating studies have shown that the osteoimmunomodulation mediated by immune cells mainly dominated by macrophages plays a pivotal role in osseointegration by releasing active factors to improve the inflammatory microenvironment. However, the mechanism by which osteoimmunomodulation mediates osseointegration remains unclear. Recent studies have revealed that exosomes released by macrophages play a central role in mediating osteoimmunomodulation. The exosomes can be internalized by various cells participating in de novo bone formation, such as endothelial cells and osteoblasts, to intervene in the osseointegration robustly. Therefore, macrophage-derived exosomes with multifunctionality are expected to significantly improve the osseointegration microenvironment, which is promising in reducing the occurrence of aseptic loosening. Based on this, this review summarizes recent studies on the effects of exosomes derived from the immune cells on osseointegration, aiming to provide a theoretical foundation for improving the clinical success rate of biomedical implants and achieving high-quality and high-efficiency osseointegration.